Mind and body practices for fatigue reduction in patients with cancer and hematopoietic stem cell transplant recipients: A systematic review and meta-analysis. (December 2017) - Duong, Nathan; Davis, Hailey; Robinson, Paula D.; Oberoi, Sapna; Cataudella, Danielle; Culos-Reed, S. Nicole; Gibson, Faith; Götte, Miriam; Hinds, Pamela; Nijhof, Sanne L.; Tomlinson, Deborah; van der Torre, Patrick; et al.
Highlights: Overall mind and body practices reduced fatigue in cancer and stem cell transplant. Mindfulness and relaxation techniques were effective in reducing fatigue. Acupuncture, acupressure, massage, and energy therapy did not reduce fatigue. Abstract: Purpose: To determine whether non-physical activity mind and body practices reduce the severity of fatigue in patients with cancer or hematopoietic stem cell transplant (HSCT) recipients compared to control interventions. Methods: We included randomized trials which compared non-physical activity mind and body practices compared with control interventions for the management of fatigue in cancer and HSCT patients. Results: Among 55 trials (4975 patients), interventions were acupuncture or acupressure (n = 12), mindfulness (n = 11), relaxation techniques (n = 10), massage (n = 6), energy therapy (n = 5), energizing yogic breathing (n = 3) and others (n = 8). When combined, all interventions significantly reduced fatigue severity compared to all controls (standardized mean difference −0.51, 95% confidence interval −0.73 to −0.29). More specifically, mindfulness and relaxation significantly reduced fatigue severity. Conclusions: Mindfulness and relaxation were effective at reducing fatigue severity in patients with cancer and HSCT recipients. Future studies should evaluate how to translate these findings into clinical practice across different patient groups.